Data in the Classroom - Steffen, Peggy (DigitalCommons@IMSA, 2020)
Put ocean data to work in your classroom. Students use real-time data to explore environmental issues such as coral bleaching, sea level rise and ocean acidification. Activities have a scaled approach from beginner to "design your own investigation" with data tools that will help students get started with online data sets. Please bring your own laptop for this session.